Association between preoperative hematocrit and postoperative 30-day mortality in adult patients with tumor craniotomy - Liu, Yufei; Li, Lunzou; Hu, Haofei; Yang, Jihu; Zhang, Xiejun; Chen, Lei; Chen, Fanfan; Hao, Shuyu; Li, Weiping; Huang, Guodong (Frontiers in Neurology, 2023)
Background: The purpose of this research was to synthesize the American College of Surgeons National Surgical Quality Improvement Program database to investigate the link between preoperative hematocrit and postoperative 30-day mortality in tumor craniotomy patients. Methods: A secondary retrospective analysis of electronic medical records of 18,642 tumor craniotomy patients between 2012 and 2015 was performed. The principal exposure was preoperative hematocrit. The outcome measure was postoperative 30-day mortality. We used binary logistic regression modeling to explore the link between them and conducted a generalized additive model and smooth curve fitting to investigate the link and its explicit curve shape. We conducted sensitivity analyses by converting a continuous HCT into a categorical variable and calculated an E-value. Results: A total of 18,202 patients (47.37% male) were included in our analysis. The postoperative 30-day mortality was 2.5% (455/18,202). After adjusting for covariates, we found that preoperative hematocrit was positively associated with postoperative 30-day mortality (OR=0.945, 95% CI: 0.928, 0.963). A nonlinear relationship was also discovered between them, with an inflection point at a hematocrit of 41.6. The effect sizes (OR) on the left and right sides of the inflection point were 0.918 (0.897, 0.939) and 1.045 (0.993, 1.099), respectively. The sensitivity analysis proved that our findings were robust. The subgroup analysis demonstrated that a weaker association between preoperative hematocrit and postoperative 30-day mortality was found for patients who did not use steroids for chronic conditions (OR=0.963, 95% CI: 0.941-0.986), and a stronger association was discovered in participants who did use steroids (OR=0.914, 95% CI: 0.883-0.946). In addition, there were 3841 (21.1%) cases in the anemia group (anemia is defined as a hematocrit (HCT) <36% in females and <39% in males). In the fully adjusted model, compared with the non-anemic group, patients in the anemic group had a 57.6% increased risk of postoperative 30-day mortality (OR=1.576; 95% CI: 1.266, 1.961). Conclusions: This study confirms that a positive and nonlinear association exists between preoperative hematocrit and postoperative 30-day mortality in adult patients undergoing tumor craniotomy. Preoperative hematocrit was significantly associated with postoperative 30-day mortality when the preoperative hematocrit was less than 41.6.